Effect of Music-Therapy on Depression of Chronic PTSD Veterans - L. Esmaeili; M.H. Pourabaian Esfahani; F. Dabbashi (Afarand Scholarly Publishing Institute, 2015)
Aims: The purpose of this research was to determine the effect of Music Therapy intervention on mental health of chronic Post-Traumatic Stress Disorder (P.T.S.D) veterans. Materials & Methods: This research was based on a semi-experimental design with pre-test, post-test and control group respectively. The population also included chronic Post Traumatic Stress Disorder (P.T.S.D) veterans Isfahan in 2013. In order to perform this study, 60 members of chronic Post-Traumatic Stress Disorder (P.T.S.D) veterans who were available selected (each group consisting 30). The tool of this research was Beckchr('39')s questionnaire of depression (Beck et. al, 1966) was used in two phases pre-test and post-test. Results: The results were analyzed by ANCOVA showed that Music Therapy intervention had a significant effect on depression in chronic Post-Traumatic Stress Disorder (P.T.S.D) veterans in post-test on experimental group (P≤0.05). Conclusion: Based on these results, music therapy can use as an effective and low cost treatment for decreasing of depression on chronic post-traumatic stress disorder (P.T.S.D) veterans.